From Stone Age to Stellenbosch : Studies on the Ancient Near East in Honour of Izak (Sakkie) Cornelius - Cornelius, Izak, 1958-; Dijk-Coombes, Renate M. van; Swanepoel, Liani C.; Kotzé, Gideon R. (Zaphon Verlag, 2021)
The Old Testament scholar Izak (Sakkie) Cornelius has devoted his ongoing scholarly career to the cultures of the ancient Near East (including North Africa and Western Asia). In accordance with a focal point of his scientific research several of the studies assembled in this festschrift are devoted to the images of the divine and to that of goddesses in particular, encompassing the antiquities of Israel/Palestine, Egypt and the Near East.
Keywords: Art, Middle Eastern.; Art, Ancient -- Middle East.; Goddesses -- Middle East; Goddesses in art.; Art moyen-oriental.; Déesses dans l'art.; HISTORY / Ancient / General; Art, Ancient; Art, Middle Eastern; Goddesses; Goddesses in art; Middle East; Festschriften; Festschriften.